2020
DOI: 10.1093/mnras/staa1342
|View full text |Cite
|
Sign up to set email alerts
|

SHARP – VI. Evidence for CO (1–0) molecular gas extended on kpc-scales in AGN star-forming galaxies at high redshift

Abstract: We present a study of the stellar host galaxy, CO (1–0) molecular gas distribution and AGN emission on 50–500 pc-scales of the gravitationally lensed dust-obscured AGN MG J0751+2716 and JVAS B1938+666 at redshifts 3.200 and 2.059, respectively. By correcting for the lensing distortion using a grid-based lens modelling technique, we spatially locate the different emitting regions in the source plane for the first time. Both AGN host galaxies have 300–500 pc-scale size and surface brightness consistent with a bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 130 publications
(195 reference statements)
4
27
0
Order By: Relevance
“…Sharon et al (2016) looked for differences between AGN and SMGs and find the two samples to be consistent in their CO and FIR properties for both CO(3-2) and CO(1-0) transitions. Conversely, Spingola et al (2020) observed two lensed AGN at z ≈ 2−3 and find larger CO(1-0) luminosities with respect to their FIR emission when compared with star-forming galaxies, meaning that they may be less efficient at forming stars.…”
Section: Comparison With Previous Workmentioning
confidence: 95%
See 2 more Smart Citations
“…Sharon et al (2016) looked for differences between AGN and SMGs and find the two samples to be consistent in their CO and FIR properties for both CO(3-2) and CO(1-0) transitions. Conversely, Spingola et al (2020) observed two lensed AGN at z ≈ 2−3 and find larger CO(1-0) luminosities with respect to their FIR emission when compared with star-forming galaxies, meaning that they may be less efficient at forming stars.…”
Section: Comparison With Previous Workmentioning
confidence: 95%
“…Some indications of this scenario at higher redshift are provided by lensed AGN. Spingola et al (2020) and Paraficz et al (2018) observed a decrease in the surface brightness of the CO(1-0) and (2-1) emission (at z ≈ 2 and 0.6), respectively, at the location of the AGN emission and the center of host galaxies. This is interpreted as a potential decrement in the molecular gas at low excitation close to the AGN possibly due to AGN radiative feedback.…”
Section: Agn Radiation Fieldmentioning
confidence: 97%
See 1 more Smart Citation
“…The core-jet system is gravitationally lensed, resulting in a complex structure stretched out along an arc of emission (Lehar et al 1997). In addition to being a source of strong radio emission, the quasar was discovered to be a source of CO molecular line emission (Barvainis et al 2002;Alloin et al 2007;Riechers et al 2011;Spingola et al 2020) as well as sub-millimetre continuum (Wu et al 2009;Stacey et al 2018).…”
Section: Mg 0751+2716mentioning
confidence: 99%
“…Many studies of radio lenses have attempted to do the same (e.g. Kochanek et al 1989;Lehar et al 1993;King et al 1997;Wucknitz 2004;Wucknitz et al 2004;Hartley et al 2019;Spingola et al 2020;Stacey et al 2020) and study the relation of the radio source components to other components of the source emitting at other wavebands. The relation of steep-spectrum, synchrotron radio components with other source components can also be investigated, given sufficient resolution at low frequency, which no instrument other than the Low-Frequency Array (LOFAR) operated by the International LOFAR Telescope (ILT) foundation is capable of providing.…”
Section: Introductionmentioning
confidence: 99%